IP restoration vs. WDM protection is there an optimal choice?. - Fumagalli, A.
The exponentially growing number of Internet users armed with emerging multimedia Internet applications is continuously thirsty for more network capacity. Wavelength-division multiplexing networks that directly support IP-the so-called IP over WDM architecture-have the appropriate characteristics to quench this bandwidth thirst. As everyday life increasingly relies on telecommunication services, users become more and more demanding, and connection reliability is currently as critical as high capacity. Both IP and WDM layers can fulfil this need by providing various resilient schemes to protect users' traffic from disruptions due to network faults. This article first reviews the most common restoration and protection schemes available at the IP and WDM layers. These schemes may be present concurrently in the IP over WDM architecture, with the resilient mechanism of each connection specifically chosen as a function of the overall cost, application requirements, and management complexity. The article describes a versatile heuristic based on simulated annealing that may be adopted to optimize the concurrent use of IP restoration and WDM protection schemes in the same (mesh) network. The proposed heuristic allows varying the percentage of traffic protected by the WDM layer and that of traffic relying on IP restoration, taking into account topology constraints and network cost minimization. An additional feature of the proposed heuristic is the potential to trade solution optimality for computational time, thus yielding fast solutions in support of interactive design.
Keywords: IP layers; IP over WDM architecture; IP restoration; WDM layers; WDM protection; Application requirements; Computational time; Connection reliability; Interactive design; Management complexity; Mesh network; Multimedia Internet applications; Network capacity; Network cost minimization; Network faults; Simulated annealing based heuristic; Telecommunication services; Topology constraints; Traffic; Wavelength-division multiplexing networks